2020
DOI: 10.1002/chem.202001242
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of Pd Aggregation on a Pyridine‐Terminated Self‐Assembled Monolayer

Abstract: By using density functional theory calculations, the initial steps towards Pd metal cluster formation on a pyridine‐terminated self‐assembled monolayer (SAM) consisting of 3‐(4‐(pyridine‐4‐yl)phenyl)propane‐1‐thiol on an Au(1 1 1) surface are investigated. Theoretical modelling allows the investigation of structural details of the SAM surface and the metal/SAM interface at the atomic level, which is essential for elucidating the nature of Pd–SAM and Pd–Pd interactions at the liquid/solid interface and gaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 66 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…Support for this model comes from a recent computational study which found a preference of the Pd to sit in between rather than on top of the pyridine rings. 14 While this model is tentative it would explain the larger, more protruding particles seen in Figs. 5e and 5g as well as the difference in the number of larger particles and breadth of particle distribution compared to differently prepared samples like the one shown in Fig.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Support for this model comes from a recent computational study which found a preference of the Pd to sit in between rather than on top of the pyridine rings. 14 While this model is tentative it would explain the larger, more protruding particles seen in Figs. 5e and 5g as well as the difference in the number of larger particles and breadth of particle distribution compared to differently prepared samples like the one shown in Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Imaging conditions and stability were substantially dependent on the details of the deposition. Since Pd and Pd/Cu metal nanoparticles adhere weakly to pyridine-terminated SAMs 14,23,24 isolated particles are easily removed by attachment to the tip. Therefore, the tip-to-sample distance was maximized by applying a high sample bias of ±1-1.5 V and a low current (<5 pA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation